INVESTIGATION OF TECHNOLOGICAL PARAMETERS OF PRODUCTION OF SOUR-MILK DRINK WITH PREBIOTIC PROPERTIES ON THE BASIS OF CAMEL MILK - Assembayeva, E.K.; Galstyan, A.G.; Seidakhmetova, Z.Zh.; Velyamov, T.M.; Nurmukhanbetova, D.E. (Academic Journal of Physical and Chemical Sciences, 2018)
One of the priority directions of the public policy in the field of healthy nutrition is the creation of a technology of breakthrough food products designed not only for differentiating human needs in food substances and energy, but also contributing to the prevention of various diseases, strengthening the protective functions of the body and adequate adaptation of human to the environment. Accordingly, a technology has been developed for the production of sour-milk drink with prebiotic properties based on camel milk. The effect of a prebiotic on the physicochemical, microbiological and organoleptic parameters of the sour-milk product was considered. The optimum dose of fructose:isomaltulose:lactulose syrup and fermentation time are established